2019
DOI: 10.1021/acs.jpclett.9b03373
|View full text |Cite
|
Sign up to set email alerts
|

Organizing Crystalline Functionalized Pentacene Using Periodicity of Poly(Vinyl Alcohol)

Abstract: Nanoparticles of acenes exhibit highly efficient intermolecular singlet fission (SF). Recent reports indicate that altering the morphology of 6,13-bis-(triisopropylsilylethynyl)­pentacene (TIPS-Pn) nanoparticles has a profound influence on their SF dynamics. Here, we show that poly­(vinyl alcohol) (PVA) induces a phase transition in preformed TIPS-Pn nanoparticles. These nanoparticles are amorphous when initially formed but crystalline after addition of PVA. Surface characterization indicates that a diffuse PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 59 publications
5
25
0
Order By: Relevance
“…This assignment agrees with several previous studies which have reported SF occurring on timescales of 1-5 ps in amorphous TIPS-Pn. 18,19,21,22,24,35 Upon decreasing NP diameter, the slower decay of singlet excitons noted above (Figures 2b and 3b) is coincident with a slower formation of the triplet ESA at 507 nm (inset of Figure 3c). This trend indicates that the overall rate of SF in these amorphous TIPS-Pn for the smaller 33 nm sample.…”
Section: Time-resolved Spectrophotometric Characterizationmentioning
confidence: 62%
See 2 more Smart Citations
“…This assignment agrees with several previous studies which have reported SF occurring on timescales of 1-5 ps in amorphous TIPS-Pn. 18,19,21,22,24,35 Upon decreasing NP diameter, the slower decay of singlet excitons noted above (Figures 2b and 3b) is coincident with a slower formation of the triplet ESA at 507 nm (inset of Figure 3c). This trend indicates that the overall rate of SF in these amorphous TIPS-Pn for the smaller 33 nm sample.…”
Section: Time-resolved Spectrophotometric Characterizationmentioning
confidence: 62%
“…As all of these processes involve intermolecular exciton interactions, it is reasonable to infer that these changes likely arise from variations in NP morphology with particle size. Previous studies have demonstrated that polymers such as PMMA or poly(vinyl alcohol) (PVA) can disrupt or alter the morphology of TIPS-Pn NPs, 21,24 while the use of other additives as surfactants or emulsifying agents has been shown to alter the intermolecular packing of other organic nanoaggregates. 44,45 However, as the preparation of the TIPS-Pn…”
Section: Changes In Nanoparticle Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous dispersions of TIPS-Pn nanoparticles (NPs) are commonly used for spectroscopic characterization of SF and associated exciton dynamics. 18,21,[23][24][25] Study of NP dispersions allows solid-state photophysical processes to be probed while using liquid-phase samples, which minimizes experimental issues associated with the study of thin films and other solidphase media such as photo-bleaching or sample opacity. Such dispersions are generally prepared through the "re-precipitation" or "flash precipitation" method first reported by Matsuda and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…TIPS-Pn NPs prepared by the re-precipitation method have been shown to form with amorphous morphologies, 18,21 although more recent studies have since demonstrated methods of converting these to crystalline structures through use of chemical additives. 19,24 Particle sizes can be readily tuned by control of re-precipitation conditions such as chromophore concentration or solvent combination, 27,28 and TIPS-Pn NPs have been reported with diameters in the range of 30-160 nm. 23,29 However, despite this wide range of NP sizes used to study SF dynamics in TIPS-Pn, the potential influence of NP size upon exciton dynamics in this system has not yet been considered.…”
Section: Introductionmentioning
confidence: 99%